Developing a web-based packet monitoring tool / Hamsiah Mohamed Said - Mohamed Said, Hamsiah (Faculty of Information Technology and Quantitative Sciences, 2006)
This project is an effort in to develop a web-based program to monitor the network traffic over a local host and a local network based on the flow of the User Datagram Protocol. This system was developed to have the feature that can show packet traffic in detail such as source and destination IP address, source and destination port number, total number of packets transferred, session and other data. Besides, it capable to capture traffic from multiple network adapters simultaneously. This monitoring tool uses the web interface so users can easily access traffic information via generic and easy to use Web browser. It also has the ability to sort and retrieve the information from database. This program will be written in java language on background process and PHP on foreground process based on Window XP Operating System platform. Throughout this report, there will be altogether 5 chapters. The first chapter will be explaining the scope and objective of this project. Second chapter focus on some definition of pertinent terminologies and other projects related to this project. The third chapter will be discussing the method being used to develop the system or program. The fourth chapter will present the results from this project and finally the overall progress and achievement of this project will be discussed in chapter five.